Survey of Wireless Communications Applications in the Railway Industry - Shafiullah, G.; Gyasi-Agyei, A.; Wolfs, Peter (University of Technology Sydney, 2007)
Advances in information and communications technology have enabled the adoption of wireless communication techniques in all sectors for the transmission of information in all forms between any two points. Wireless communications and distributed computing have promoted the development of vehicle- monitoring systems to reduce the maintenance and inspection requirements of railway systems while maintaining safety and reliability. This paper surveys existing wireless techniques used in the railway industry for both communications and signalling purposes. Finally we present our work in progress on low-cost, low-power wireless sensor networking architecture to monitor the health of railway wagons attached to a moving locomotive.